Memory wars in the Low Countries, 1566-1700 - Steen, Jasper van der (Studies in medieval and Reformation traditions, 2015)
"The Revolt in the Netherlands erupted in 1566 and tore apart the Low Countries. In Memory Wars in the Low Countries, 1566-1700 Jasper van der Steen explains how public memories of the Revolt in the Habsburg Netherlands in the South and the Dutch Republic in the North diverged and became the objects of fierce contestation in domestic political struggles, on both sides of the border and throughout the seventeenth century. Against widespread assumptions about the supposed modernity of cultural memory Memory Wars argues that early modern public memory did not require the presence of state actors, nationalism and modern mass media in order to play a role of political importance in both North and South"--